URGENSI PENDIDIKAN ISLAM DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL - Azma N. Mardjun (Hunafa: Jurnal Studia Islamika, 2007)
This essay deals with the urgency of Islamic education in developing emotional quotient. Islamic education is concerned  about not only physical development but also inner capacity of human beings. Today, many people become highly educated in the sense that they possess a high intelligence quotient but a low spiritual quotient. As a result, they tend to commit immoral deeds. It is regulated in Islam, therefore, that a soul has both negative effect and positive effect. However, the negative effect of emotion can be managed so that it can be effective.  Therefore, people should posses not only intelligence quotient but also emotional quotient. The purpose is to enable them to attain the equilibrium of their life.      Kata Kunci:  pendidikan Islam, kecerdasan emosional